Перспективные материалы для низкоомных толстопленочных резистивных элементов - Smirnov, A. N.; Puchkova, N. S.; Sidorets, R. G.; Lemza, V. D. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The development of highly stable low-resistance variable resistors using thick-film technology is discussed. A paste system based on Ag/Ru/Pd with 35–45% glass binder content provides excellent surface properties and technological characteristics of the resistors. The ability to obtain intermediate values of specific resistance expands the possibilities for designing microassemblies and applying thick-film technology in new areas of engineering.